Minimum inhibitory concentrations of erythromycin and rifampin for Rhodococcus equi during the years 2007–2014 - Fenton, Caitriona S. (Ir Vet J, 2015)
BACKGROUND: Rhodococcus equi is a gram positive, intracellular pathogen of foals worldwide. The aim of this study was to determine whether there was an increasing resistance occurring in Rhodococcus equi towards the antibiotics rifampin and erythromycin over a seven year period. The investigation was carried out with the use of E test strips (epsilometers) for rifampin and erythromycin in order to determine the Minimum Inhibitory Concentrations (MIC) values of Rhodococcus equi to these antibiotics. RESULTS: The main results of this study found that the mean MICs were higher for erythromycin than for rifampin for every year analysed apart from 2008. The results highlight that 75 % (6/8) of the mean MICs for erythromycin were above the threshold of susceptibility of 0.5 μg/ml and one of the yearly mean MICs for rifampin (2008) was above the level of ≤ 1 μg/ml. Two soil samples analysed had high MIC values of 2 μg/ml and 3 μg/ml for rifampin and erythromycin respectively. These samples can be said to have acquired resistance as they are above 1 μg/ml. CONCLUSIONS: The significance of these findings is that R. equi is already a problematic pathogen to treat and if the bacteria keeps gaining resistance to these antibiotics at rate that has been shown over the last decade, then a new form of treatment will have to be introduced. Further research into the genomics of Rhodococcus equi will, in time, shed more light on possible alternatives such as vaccines or new, more effective antimicrobials.